Geochemistry on manganese nodules from the Pacific - Jane Z Frazer; Mary B Fisk; R Fitzgerald; J Guy (PANGAEA, 1984)
Manganese nodules have been analysed at the Scripps Institution of Oceanography after having been ground to to a diameter less than 74 microns. Some analysises were performed on pellets by X-ray Emission Spectroscopy for 1000 Seconds. All concentrations have been corrected to 110 degrees Celsius drying conditions (see: https://doi.pangaea.de/10.1594/PANGAEA.854202).
Supplement to: Frazer, JZ et al. (1976): Chemical analyses of manganese nodules, 1975-1976. Scripps Institution of Oceanography, UC San Diego Report, unpublished